Leadership talk a discourse approach to leader emergence - Walker, Robyn; Aritz, Jolanta 1968- (Corporate communication collection, 2014)
1. Introduction to discursive leadership -- 2. Introduction to the elements of leadership -- 3. Leadership communication styles -- 4. Leading employees -- 5. Cross-cultural leadership -- 6. Gender and leadership -- 7. Applying the discursive approach and beyond -- Notes -- References -- Index